Analysis of the Web Development of Piksi Ganesha Polytechnic Campus Students With the Integration of the MBKM Program Menu in the Student Information System Project - Pasaribu, Johni S; Tamami, Arum (International Journal of Engineering, Science and Information Technology, 2024)
The development of information technology has had a significant impact on higher education, with the campus web becoming one of the main means for interaction and access to information. Politeknik Piksi Ganesha as a progressive educational institution has modernized student services and data management and modified the previously existing web through the student information system (SIM-SIS) project. This study aims to analyze the development of the Piksi Ganesha Polytechnic campus student web with the integration of the Merdeka Belajar Kampus Merdeka (MBKM) program menu in the Student Information System (SIM-SIS) project. In this study, the authors used the waterfall model as a web development model for students of the Piksi Ganesha Polytechnic campus. The result of this study indicate that the integration of the MBKM program menu on SIM-SIM provides a significant increase in the accessibility of information and management of the Merdeka Belajar Kampus Merdeka program for the students. The implications of this research contribute to the understanding and development of educational information systems in the campus environment, and provide a basis for futher improvement in campus web development